Charting and shaping the modern consumer. The rise of customer research in the Dutch department store De Bijenkorf, 1930-1960 - Jan Hein Furnée (BMGN: Low Countries Historical Review, 2017)
In the decades before and after World War ii, major European department stores were increasingly eager to know and understand their customers. This article analyses how the Dutch department store De Bijenkorf, in dialogue with leading European partners, developed a wide range of research techniques to chart the social composition and buying behavior of its customers in order to enhance the company’s efficiency in procurement, advertising, spatial organization and sales. The customer research of De Bijenkorf helped to legitimize new business policies such as up- and downtrading and impulse buying, but also reflected and established new ideas and images of modern urban consumers as statistical categories behaving in astonishing regular ways.   This article is part of the special issue on consumption history.